THE IMPLEMETATION OF THE ACCOUNTING STANDARDS PSAK 73 LEASES TO THE FINANCIAL PERFORMANCE OF COMPANIES LISTED ON THE STOCK EXCHANGE. - Ayunita Ajengtiyas Saputri Mashuri; Husnah Nur Laela Ermaya (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2021)
PSAK 73 is the latest accounting standard about lease accounting, this standard was adopted from IFRS 16. PSAK 73 regulates the arrangement, measurement, presentation and disclosure of leases, both Lessee and Lessor. This paper aims to provide information on the proposed new lease accounting rules, and to show their impact on financial statements and financial ratio on Indonesia companies listed. The difference between PSAK 73 and the previous PSAK 30, lies in the recognition of the lessee. Lessess are only allowed to classify leases as financing leases. Thus, that assets and liabilities for lease transactions have to recognized in the statement of financial position. This study aims to analyze the impact of the adoption of new accounting standards namely PSAK 73 regarding leases on the financial performance of companies listed on the Indonesia Stock Exchange in 2018 and 2019. The sample in this study are companies that are still implementing operating leases in their financial statements listed on the Exchange Indonesian Stock Exchange in 2018-2019. This study uses the constructive capitalization method of rent developed by Imhoff, Lipe and Wright (1991). The results are indicate that the impact of leasing capitalization results will have a material changes reported on the income statement and other comprehensive income and Financial Position reporting. And the results of this study also mentioned that there was a significant change in financial performance measured using financial ratio which are bring benefit in decision making.